1995
DOI: 10.1017/s0033291700035030
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bipolar disorder and alcoholism: a controlled family study

Abstract: SYNOPSISBipolar disorder and alcoholism are familial disorders. The familial–genetic relationship between both is controversial and has received insufficient study. This study explores whether bipolar disorder and alcoholism share familial risk factors, and whether the co-occurrence of lifetime diagnosis of bipolar disorder and alcoholism is familial. We report on first-degree relatives of 146 consecutively admitted patients with either bipolar disorder or/and alcoholism; relatives of the patients (in total 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…However, lifetime prevalence of AUDs was reported by 31 independent clinical studies [8,63,7,3,5,4,9,12,15,18,22,24,28,32,33,55,[38][39][40][42][43][44][45][46][47]49,56,58,60,61,67], including 8309 subjects with BD, allowing us to calculate pooled lifetime prevalence.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lifetime prevalence of AUDs was reported by 31 independent clinical studies [8,63,7,3,5,4,9,12,15,18,22,24,28,32,33,55,[38][39][40][42][43][44][45][46][47]49,56,58,60,61,67], including 8309 subjects with BD, allowing us to calculate pooled lifetime prevalence.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Information on gender was presented in 17 of the clinical studies we identified [63,5,12,15,28,32,[38][39][40]42 (Fig. 2).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Therefore the presence of one disorder may indicate an increased risk of the second. 22 For example, excess co-morbidity between bipolar disorder and alcoholism has been observed. The two disorders may share a common risk factor or factors that may be familial and therefore the presence of one disorder may indicate an increased risk of the second.…”
Section: Alcohol Use Disordersmentioning
confidence: 99%
“…The two disorders may share a common risk factor or factors that may be familial and therefore the presence of one disorder may indicate an increased risk of the second. 22 Alcoholism may cause relapse in depressed patients and contributes to the course of the depressive illness. Depression, which has been successfully treated, may be relapsed by alcoholism.…”
Section: Alcohol Use Disordersmentioning
confidence: 99%
“…The high magnitude of comorbidity and co-aggregation of index disorders with other major psychiatric disorders (bipolar disorder and alcoholism, major depression and anxiety disorders, schizophrenia and drug dependence), in part induced by the classification system, as described previously, has been another impediment to identifying pathogenetic mechanisms for mood disorders [119][120][121][122][123][124]. For example, alcoholism, a well-established complication of bipolar illness, may mask the underlying features of bipolarity, leading to phenotypic misclassification in genetic studies [125].…”
Section: Impediments To Identification Of Genes For Mood Disordersmentioning
confidence: 99%